Inflation, Exchange Rates and PPP in a Multivariate Panel Cointegration Model - Tor Jacobson; Johan Lyhagen; Rolf Larsson; Marianne Nessén (Sveriges Riksbank, 2002)
New multivariate panel cointegration methods are used to analyze nominal exchange rates and prices in four major economies in Europe; France, Germany, Italy and the United Kingdom for the post-Bretton Woods period. We test for purchasing power parity between these four countries and find that the theoretical PPP relationship does not hold. However, the estimated unrestricted relationship is found to be remarkably close to the theoretical one (1,-1.5,0.9 instead of 1,-1,1). Relevant asymptotic results are stated, proved, and evaluated using Monte Carlo simulations. The asymptotic results are general and may hence be used in similar empirical contexts using the same model structure. Parametric bootstrap inference is used in order to deal with test size distortions.
Keywords: C15; C32; F30; 330; Panel data; long-run purchasing power parity; multivariate cointegration analysis; bootstrap inference